2017
DOI: 10.1186/s13756-017-0266-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum and metalo beta-lactamase producing airborne Pseudomonas aeruginosa and Acinetobacter baumanii in restricted settings of a referral hospital: a neglected condition

Abstract: BackgroundFrequently encountered multidrug-resistant bacterial isolates of P. aeruginosa and A. baumannii are common and prevalent in a hospital environment. The aim of this study was to determine the prevalence and pattern of antibiotic resistance, extended spectrum and metallo beta-lactamase producing P. aeruginosa and A. baumannii isolates from restricted settings of indoor air hospital environment.MethodsA hospital-based cross-sectional study was conducted in Wolaita Sodo University Teaching and referral H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
28
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 25 publications
20
28
10
Order By: Relevance
“…The proportion of nosocomial MDR A. baumannii infection (3.8%) in the present study was in agreement with earlier studies conducted in Africa (2.4-5.7%) [26,29,32]. However, it was lower compared with findings from Sodo (15.3%), Ethiopia [18] and Gaza city (6.9%) [28]. In contrast, it was higher than findings from previous studies in elsewhere (0.42-0.95%) [27,30].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The proportion of nosocomial MDR A. baumannii infection (3.8%) in the present study was in agreement with earlier studies conducted in Africa (2.4-5.7%) [26,29,32]. However, it was lower compared with findings from Sodo (15.3%), Ethiopia [18] and Gaza city (6.9%) [28]. In contrast, it was higher than findings from previous studies in elsewhere (0.42-0.95%) [27,30].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the magnitude of nosocomial MDR P. aeruginosa infection (4.6%) in the present study was comparable with a study in Uganda (5%) [26]. However, it was lower than findings from other parts of Ethiopia (11.1-66.7%) [8,18,25], Ghana (19.5%) [32], India (76.8%) [39] and Italy (8.7%) [27]. In contrast, it was higher compared to a study in China (0.36%) [30].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Those patients infected with carbapenem resistant strains have a 35.2% proportional chance of cure with these honored drugs and seeks for easily inaccessible drug colistin and resistant to 25.2% of those who had the chance in the poor nations of Eastern Africa.The surgical site infections due A. baumannii in Ethiopia shown that 34.8% of the isolates were pan-resistant, unable to treat with locally available treatment options leading for unnoticed death(30). Similarly, 16.3% of isolates from the operation theatre and delivery rooms were responsible for untreatable infections to patients attending hospitals of Ethiopia(45). Whereas, in Uganda 55% of hospital environment isolates were resistant for carbapenem looking for the unavailable and 25.2% proportionally resistant drug, colistin(29).…”
mentioning
confidence: 99%